Emerging climate changes and the risks to the operation of building assets in the UK. Issue 1 (1st February 2016) - Alzahrani, Abdullah; Boussabaine, Halim; Alzaed, Ali Nasser
Abstract : Purpose: – The purpose of this paper is to report results from a survey on emerging climate changes and the risks to the operation of building assets in the UK. The property sector is facing major challenges as a result of projected climate change scenarios. Predictions concerning future climate change and the subsequent impact on building operations are still subject to a high degree of uncertainty. However, it is important that building stockholders consider a range of possible future risks that may influence the operation of their assets. Design/methodology/approach: – The literature review and questionnaire are used to elicit and assess the likelihood of occurrence of climate change risks impacting building operations. The survey was carried out among building stockowners and professionals in the UK. Statistical methods were used to rank and compare the findings. Findings: – The majority of the respondents strongly agreed that the list of risks that were elicited from the literature will have an impact on their building assets within a 0-5 years' time horizon. It was found that the professionals were most concerned about higher energy prices and an increase in operation costs in general; they were least concerned about an electricity blackout. Research limitations/implications: – This paper is limited to the UK, and regional variations are not explored. Nevertheless, the buildings' operation risk study provides a starting point for further investigations into the emerging risks from climate change, and their impact on the operation of building stock. Future work could investigate direct mapping between climate risks and the financial value of properties. Originality/value: – Findings of this paper can help professionals and building stockowners improve their understanding of climate change risks and the impact on their assets. This paper could also help these individuals to formulate appropriate adaptation and mitigation strategies.